Quadro editorial (Estudos em Design, 2023)
EditoresCristina PortugalRita Maria de Souza CoutoAvaliadores desta edição v. 31, n. 2 (2023)Adriana GralowAdriana Sampaio LeiteAlexandre FarbiarzAlexandre OliveiraAline SaviÁlvaro SousaAna Beatriz Pereira de AndradeAna BerwangerAna PazminoAndré Ribeiro de OliveiraAndréa AlmeidaAndréa SilvaAngelica Adverse Antonio Colchete Filho Beany MonteiroCarlo FranzatoCassia Carrara DomicianoCayley GuimaraesCristiane Aun BertoldiCyntia Malaguti de SousaDeborah ChristoDaniel PortugalDaniel RaposoDaniela Estaregue AlvesDebora BuonanoDenise PortinariDoris KosminskyEdson RufinoEmília DuarteEverton da SilvaFernanda CardosoFernando FoglianoFilipe Campelo Xavier da CostaFrederico BraidaGabriel PatrocinioGabriela PerryGiselle MerinoGuilherme E nglert Corrêa MeyerHelena BarbosaIone BentzJade PiaiaJoana ContinoJoão SobralKarina Porto BontempoKando FukushimaKátia Carvalhaes PêgoKlaus AlbertoLaura MartinsLuiz Antonio de SaboyaLivia Flavia CamposLuiza Falcão Soares CunhaMarcelo ForcatoMarcio GuimarãesMarcos BragaMaria Do Carmo Gonçalves CurtisMaria Teresa LopesMarilda Lopes Pinheiro QueluzMariano Lopes de Andrade Neto Marina KunstMaristela OnoMaurício Klafke DickNelson KuwaharaOlavo NetoPaula Piva LinkeRafael EfremRafaella PeresRaimundo Diniz Ranielder de FreitasRavi PassosRenata WanderleyRogério CamaraSandra Maria SouzaSérgio Luciano da SilvaTiago SilvaWagner BandeiraWalter CorreiaVagner GodóiWalter NetoVera DamazioVerônica FreireVirginia KistmannViviane Nunes